[Illustration of Conchubhar, grabbing a young boy by the wrist while in the background a group of young men appear to take fright; in the right foreground another man who had been playing a board game with Conchubhar, observes the scene]. - Fagan, George, 1879-1907.; Holloway, Joseph, 1861-1944 (1905)
Black and white illustration on card signed "Ua Fágáin.'05" at lower right within image. Caption written in Cló Gaelach underneath illustration reads: "Fan go [...], a bhuacaill "atta Conchubhar "caidé an t-érthleach é reo agat ar na hógánachubh?".
Name of the artist signed in Cló Gaelach at lower right within image.
Keywords: Ink drawings -- Irish -- 1900-1910; Pen works -- Irish -- 1900-1910